COVID-19 infection in patients with chronic myeloid leukemia in the Orenburg region during the SARS-CoV-2 pandemic - G. B. Kuchma; U. A. Yakubova; L. K. Kozlova; S. A. Lebedenko; F. R. Sayfutdinov (Онкогематология, 2022)
Background. Oncohematological patients are more predispose to SARS-CoV-2 infection than healthy individuals and patients with malignant neoplasms, and also they have a worse prognosis, which is because of immune system disorders, both due to the underlying disease and as a result of immunosuppressive therapy. There is limited data regarding the impact of SARS-CoV-2 infection on the survival of patients with chronic myeloid leukemia (CML).Aim. To evaluate the course and outcome of COVID-19 in patients with CML in the Orenburg region during the SARS-CoV-2 pandemic.Materials and methods. All 166 patients with CML over 18 years of age were analyzed during the COVID-19 pandemic between february 2020 and December 2021. The source of information was data from the personalized register of patients with CML and the unified state health information system.Results. The proportion of SARS-CoV-2 infection among patients with CML was 36 %. The risk of infection was not affected by age, gender, work features, place of residence, phase or duration of the disease, and therapy. underwent COVID-19 patients were 1.6 times more likely to be overweight and 2 times more likely to have a second cancer. A significant increase in the number of outpatient visits to polyclinics and number of hospital admissions during the pandemic was revealed in the group of patients who had SARS-CoV-2 infection. underwent COVID-19 patients were over 60 years of age in 48.3 % of cases and had one or more comorbidities in 77.6 % cases. SARS-CoV-2-infected patients with CML had a favorable outcome: a mild course of infection in 75.9 % of cases and a low mortality rate - 6.8 % (4 of 58 patients) were observed. COVID-19 was recognized as the cause of death in only 2 patients with optimal molecular response and comorbidity. In two other patients who underwent COVID-19, the progression of CML to a blast crisis was recognized as the cause of death. There were no significant differences in mortality level in the group of patients who had SARS-CoV-2 infection and those who did not have COVID-19.Conclusion. patients with CML living in the Orenburg region have a low susceptibility to SARS-CoV-2 infection and a mild course of the disease. The mortality rate for CML patients infected with SARS-CoV-2 was 6.8 %. unfavorable factors in the overall survival of patients with CML infected with SARS-CoV-2 were high comorbidity and blast crisis. Reducing the number of outpatient visits during the pandemic and using remote medical consultations is likely to reduce the risk of SARS-CoV-2 infection.